METAMODELING FOR VARIABLE ANNUITIES - Gan, Guojun, 1979-; Valdez, Emiliano A. ([S.l.] : CRC PRESS, 2019)
This book is devoted to the mathematical methods of metamodeling that can be used to speed up the valuation of large portfolios of variable annuities. It is suitable for advanced undergraduate students, graduate students, and practitioners. It is the goal of this book to describe the computational problems and present the metamodeling approaches in a way that can be accessible to advanced undergraduate students and practitioners. To that end, the book will not only describe the theory of these mathematical approaches, but also present the implementations.
OCLC-licensed vendor bibliographic record.
Keywords: Variable annuities; Annuities -- Mathematical models; MATHEMATICS / General; MATHEMATICS / Probability & Statistics / General; REFERENCE / General